The Edinburgh companion to modernism and technology - Goody, Alex; Whittington, Ian (Edinburgh : Edinburgh University Press, 2022)
The first comprehensive reference book to define and delineate the intersections of modernism and technology.
eBooks on EBSCOhost
Keywords: Literature, Modern -- 20th century -- History and criticism; Modernism (Literature); Literature and technology; Littérature -- 20e siècle -- Histoire et critique; Modernisme (Littérature); Littérature et technologie; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literature and technology; Literature, Modern; Modernism (Literature); 1900-1999; Criticism, interpretation, etc